Purity and resentment in newspapers: the arrival of modern mathematics in Brazil - Siqueira, Rogério Monteiro da (Circumscribere International Journal for the History of Science, 2010)
This paper discusses some articles published in the lay media by two influential Brazilian scientists: Manoel Amoroso Costa (1885-1928) and Newton Affonso Carneiro da Costa (1929- ). These articles show that the subjects typically addressed in studies of logic and philosophy of mathematic were similar to the European ones, however, from a very particular perspective. They were mainly made by engineers, and published in media not devoted to pure mathematics. Moreover, a large part of the public attentive to modern mathematics in Brazil was lay.